Conversion of Gastrointestinal Somatostatin-Expressing D Cells Into Insulin-Producing Beta-Like Cells Upon Pax4 Misexpression - Garrido-Utrilla, Anna; Ayachi, Chaïma; Friano, Marika Elsa; Atlija, Josipa; Balaji, Shruti; Napolitano, Tiziana; Silvano, Serena; Druelle, Noémie; Collombat, Patrick (Frontiers in Endocrinology, 2022)
Type 1 diabetes results from the autoimmune-mediated loss of insulin-producing beta-cells. Accordingly, important research efforts aim at regenerating these lost beta-cells by converting pre-existing endogenous cells. Following up on previous results demonstrating the conversion of pancreatic somatostatin delta-cells into beta-like cells upon Pax4 misexpression and acknowledging that somatostatin-expressing cells are highly represented in the gastrointestinal tract, one could wonder whether this Pax4-mediated conversion could also occur in the GI tract. We made use of transgenic mice misexpressing Pax4 in somatostatin cells (SSTCrePOE) to evaluate a putative Pax4-mediated D-to-beta-like cell conversion. Additionally, we implemented an ex vivo approach based on mice-derived gut organoids to assess the functionality of these neo-generated beta-like cells. Our results outlined the presence of insulin+ cells expressing several beta-cell markers in gastrointestinal tissues of SSTCrePOE animals. Further, using lineage tracing, we established that these cells arose from D cells. Lastly, functional tests on mice-derived gut organoids established the ability of neo-generated beta-like to release insulin upon stimulation. From this study, we conclude that the sole misexpression of Pax4 in D cells appears sufficient to convert these into functional beta-like cells, thus opening new research avenues in the context of diabetes research.